2015
DOI: 10.1074/jbc.m115.636324
|View full text |Cite
|
Sign up to set email alerts
|

Rab11-dependent Recycling of the Human Ether-a-go-go-related Gene (hERG) Channel

Abstract: Background:The hERG-encoded potassium channel I Kr is important for cardiac repolarization. Results: Internalized hERG channels are recycled back to the plasma membrane through a Rab11-associated pathway. Conclusion: Recycling plays an important role in the homeostasis of hERG channels. Significance: Identification of hERG recycling is useful for understanding hERG dysfunction and for developing new strategies to rescue hERG function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…To examine the role of Rab11 in the CNO-mediated increase in I hERG , we interfered with Rab11 function by overexpressing a Rab11 DN mutant (Rab11 S25N) in M3Darr-transfected hERG-HEK cells and examined the effect of CNO on I hERG . Overexpression of Rab11 DN reduced I hERG in control cells, indicating that Rab11-contributed hERG homeostasis had been disrupted (Chen et al, 2015). Moreover, overexpression of the Rab11 DN mutant abolished the CNOinduced increase in I hERG (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…To examine the role of Rab11 in the CNO-mediated increase in I hERG , we interfered with Rab11 function by overexpressing a Rab11 DN mutant (Rab11 S25N) in M3Darr-transfected hERG-HEK cells and examined the effect of CNO on I hERG . Overexpression of Rab11 DN reduced I hERG in control cells, indicating that Rab11-contributed hERG homeostasis had been disrupted (Chen et al, 2015). Moreover, overexpression of the Rab11 DN mutant abolished the CNOinduced increase in I hERG (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…**P , 0.01 versus control (Ctrl). b-Arrestin-Mediated hERG Regulation 2013; Chen et al, 2015). It was also reported that stimulation of PIKfyve enhances Rab11-mediated transport of KCNQ1/KCNE1 channels to the membrane (Seebohm et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to accelerating internalization, ubiquitination of misfolded hERG was found to impair endocytic recycling. It was recently shown that internalized hERG is recycled by a Rab11-dependent mechanism (Lamothe & Zhang, 2013;Chen et al 2015). It is possible that ubiquitination impairs this process, although the involvement of other recycling pathways for internalized hERG channels cannot be ruled out.…”
Section: Peripheral Quality Controlmentioning
confidence: 99%
“…hERG channels are transcribed in the nucleus; after folding and assembly properly with the assistance of chaperones at the ER (135 kDa), hERG channels enter the Golgi for proper glycosylation (155 kDa) and are finally trafficked to the cell membrane for function [11]. The density of hERG channels on the plasma membrane is controlled by a balance between anterograde trafficking and retrograde degradation [12]. Here, we demonstrate that THIO reduces hERG membrane expression by inhibiting forward trafficking from the ER to the cell surface and subsequently promoting mature channel degradation.…”
Section: Introductionmentioning
confidence: 99%